The correlation between combined nasal and throat swab and chest CT findings in the diagnosis of COVID 19 - Torun, Mumtaz Taner; Durmaz, Dilber (Annals of Medical Research, 2022)
Aim: COVID-19 has spread rapidly, caused a pandemic and become a serious public health problem all over the world. The aim of the study is to investigate whether reverse transcriptase-polymerase chain reaction (RT-PCR) method, the most commonly used method for the diagnosis of COVID-19, correlate with the chest CT findings.Material and Methods: The file records of the patients with COVID-19 and suspected COVID-19 were examined retrospectively between 11 March and 30 August 2020 after the approval of the local ethics committee. Patient files were divided into 2 groups. RT-PCR negative patients were in group 1 and RT-PCR positive patients were in group 2. Combined nose and throat swab (CNTS) was used for swab sampling.Results: Of the 492 patients included in the study, 277 were men and 215 were women, with an average age of 57.45 ± 19.83. While there were 81 (29.2%) patients with chest CT findings compatible with COVID-19 in the first group, there were 80 (37.2%) patients in the second group. While the number of patients whose chest CT findings were incompatible with COVID-19 was 196 (70.8%) in group 1, it was 135 (62.8%) in group 2. There was a poor agreement between chest CT and RT-PCR in diagnosing COVID-19 (p = 0.062).Conclusion: To diagnose the disease is the most important step in treatment management. Especially in patients with incompatible RT-RCR and chest CT, the diagnosis should be strengthened by evaluating the laboratory findings and clinical symptoms of the patient.
Keywords: COVID-19; combined nasal & throat swab; RT-PCR; chest CT